Performance Analysis of Methanol in Heat Pipe Heat Exchanger – An Experimentation and Numerical study using ANFIS. Issue 1 (1st July 2022) - Ramkumar, P.; Ramasamy, S.; Kajavali, A.; Vivek, C.M.; Sivasubramanian, M.
Abstract: In electronic cooling systems and utilization of waste heat to safeguard the electronic components from overheating the heat pipe are used. This study focus with the experimentation and numerical comparison of an Heat Pipe Heat Exchanger (HPHE) using methanol. The investigation focuses on various orientation angles (0° and 90°) and extended with (10° to 80°) angles. The maximum Reynolds number obtained as 1.33% for 0° than 90°, similarly 8.56% for 60° comparing with 10°. The minimum thermal resistance obtained as 2.65% for 0° than 90°, similarly 3.81% for 60° while related with 10°. The observed average minimum thermal resistance for experimental value as 3.29% and predicted value as 3.46%. From the investigation it's evident that experimental results are closes to the numerical values using ANFIS - Neuro fuzzy system. In the utilization of waste heat recovery system the HPHE shows better performance and this can scaled and utilized for electronic component cooling applications.